CHAPTER 4. ETHICAL PROBLEMS OF DIGITALIZATION OF DOMESTIC SOCIETY IN CONDITIONS OF ACCELERATED SOCIAL DYNAMICS - ЗОРКІН, Роман (Epìstemologìčnì doslìdžennâ u fìlosofìï, socìalʹnih ì polìtičnih naukah (Online), 2025)
It is determined that in the conditions of accelerated social dynamics, specific ethical problems of digitalization of Ukrainian society arise. It is noted that digitalization is one of the determining factors of accelerated social dynamics in the modern world, constituting one of the key vectors of its development, as it creates new opportunities for the progress of humanity in various spheres of life, but, at the same time, it also causes numerous ethical challenges, which requires adequate decisions from the scientific community, state leadership, and the civil sector regarding the ethical regulation of digital transformation.